Placental Insufficiency In Term And Post-Term Gestation With Normal Fetal Growth And Adverse Displacement - Castillo-Urquiaga, Walter (2017)
Objective. To know the indicators of placental insufficiency in term and post - term gestation with normal fetal growth and adverse outcome in the National Maternal Perinatal Institute during the year 2017. Materials and methods. A correlational, descriptive, cross-sectional and retrospective study was performed in 37-42 weeks' pregnant women with normal umbilical Doppler and normal fetal growth. We investigated the association between eight indicators and six adverse outcomes for placental insufficiency.